#### Answer

83

#### Work Step by Step

We are given that $f(x)=x^{2}+4$, $g(x)=2x+3$, and $h(x)=x-5$.
We are asked to find $(g∘f)(6)$. We know that $(g∘f)(x)=g(f(x))$.
Therefore, $(g∘f)(6)=g(f(6))=g(6^{2}+4)=g(36+4)=g(40)=2(40)+3=80+3=83$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

83

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.